(untitled) (Research Journal, 2024)
In an era of rising worldwide complexity and accountability, civil society organizations (CSOs) have emerged as a critical component in defining the quality of governance in democratic systems. This article addresses the interrelationship between civil society and good governance, focusing on their interdependence and the implications for democratic countries. Civil society, which includes non-governmental organizations, advocacy groups, and grassroots movements, plays an important role in defining governance quality and acting as a link between the state and its citizens. Transparency, accountability, commitment to the rule of law, and active public involvement are all principles of good government. Civil society organizations raise crucial concerns and advocate for policy reform, helping government institutions to be more effective and legitimate. The study relies on qualitative research methods and secondary data sources, emphasizing the importance of civil society engagement and effective governance in sustaining democratic values and promoting equality for all.